Switching from a preserved to a preservative‐free prostaglandin preparation in topical glaucoma medication - Uusitalo, Hannu; Chen, Enping; Pfeiffer, Norbert; Brignole‐Baudouin, Françoise; Kaarniranta, Kai; Leino, Markku; Puska, Päivi; Palmgren, Elina; Hamacher, Thomas; Hofmann, Günter; Petzold, Gernot; Richter, Ulrich; et al. (Acta ophthalmologica (Oxford, England), 2010)
. Purpose:  The purpose of this study was to investigate the tolerability and intraocular pressure (IOP) reducing effect of the first preservative‐free prostaglandin tafluprost (Taflotan®) in patients exhibiting ocular surface side‐effects during latanoprost (Xalatan®) treatment. Methods:  A total of 158 patients were enrolled in this open‐label multicentre study. Eligible patients had to have at least two ocular symptoms, or one sign and one symptom, during treatment with latanoprost. At baseline, the patients were directly switched from latanoprost to preservative‐free tafluprost for 12 weeks. The patients were queried for ocular symptoms, and ocular signs were assessed by using tear break‐up time, Schirmer’s test, fluorescein staining and evaluation of conjunctival hyperaemia and blepharitis. In addition, HLA‐DR and MUC5AC in conjunctival impression cytology specimens were analyzed, and a drop discomfort/quality of life (QoL) questionnaire was employed. IOP was measured at all visits. Results:  Preservative‐free tafluprost maintained IOP at the same level after 12‐ weeks treatment (16.4 ± 2.7 mmHg) as latanoprost at baseline (16.8 ± 2.5 mmHg). During treatment with preservative‐free tafluprost, the number of patients having irritation/burning/stinging (56.3%), itching (46.8%), foreign body sensation (49.4%), tearing (55.1%) and dry eye sensation (64.6%) decreased to 28.4%, 26.5%, 27.1%, 27.1% and 39.4% correspondingly. The number of the patients with abnormal fluorescein staining of cornea (81.6%) and conjunctiva (84.2%), blepharitis (60.1%), conjunctival hyperaemia (84.2%) and abnormal Schirmer’s test (71.5%) was also reduced significantly to 40.6%, 43.2%, 40.6%, 60.0% and 59.4% correspondingly. The tear break‐up time improved significantly from 4.5 ± 2.5 seconds to 7.8 ± 4.9 seconds. A reduction in the number of patients with abnormal conjunctival cells based on HLA‐DR and MUC5AC was also detected. Conclusions:  Preservative‐free tafluprost maintained IOP at the same level as latanoprost, but was better tolerated in patients having signs or symptoms while on preserved latanoprost. Preservative‐free tafluprost treatment resulted in improved QoL, increased patient satisfaction and drop comfort.